Apoptosis in the endometrium of postmenopausal women receiving tibolone - (:unkn) unknown (KARGER, 2003)
Background/Aim: Tibolone, a synthetic derivative of the 19-nortestosterone family, induces atrophy of the endometrium, especially via its progestogenic Delta(4) isomer. The aim of the study was to determine whether tibolone induces apoptosis in the endometrium of postmenopausal women. Methods: Twenty healthy postmenopausal women (mean age+/-SD 52.4+/-4.21 years) who had amenorrhea for at least 1 year and who had no history of any systemic illness and estrogen replacement therapy were enrolled in the study. All patients were offered office endometrial samplings, and then tibolone was prescribed (2.5 mg/day p.o., once daily) to all patients. Repeat endometrial samples were obtained after completion of the 6-month course of tibolone therapy. All samples were immunohistochemically analyzed for the presence of apoptotic cells. Results: There was no significant difference in the median proportion of apoptotic nuclei between the pre- and posttreatment samples (2 vs. 3%; p>0.05). Conclusions: The results showed that tibolone did not affect the rate of apoptosis in the postmenopausal endometrium. Further studies are needed to clarify the role of apoptosis in overall effects of hormonal compounds on the postmenopausal endometrium. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: apoptosis; endometrium; postmenopausal women; tibolone; BREAST-CANCER CELLS; BCL-2 EXPRESSION; PROLIFERATION; PROGESTIN